Cyanidium caldarium (Tilden) geitler (Cyanidiaceae, Cyanidiophyceae) nueva cita para la flora algal continental española - García-Fernández, María Eugenia; Aboal, Marina (Acta Botanica Malacitana, 2011)
Cyanidium caldarium (Tilden) Geitler (Cyanidiaceae, Cyanidiophyceae) new record for the Spanish continental algal flora Palabras clave. Cyanidiophyceae, Cyanidium, cuevas, aguas termales, material yesífero, distribución. Keywords. Cyanidiophyceae, Cyanidium, caves, thermal springs, gypsum, distribution.